Judical Review on The Authority of Subdistrict Head as A Temporary Land Deed Officials in The Making of Deed in Bojong Subdistrict, Tegal Regency - Muhammad Muamal; Khanafi Khanafi; Amin Purnawan (Jurnal Akta, 2018)
The Sub-district head is appointed as temporary PPAT based on the provisions of the Act. It is due to there is not enough PPAT in the government area, so the government gives authority to the Sub-district head to serve the community in making deeds related to the transfer of Land Rights. In reality, not all sub-district heads are able to carry out their duties and authority. The constraints are due to the lack of Sub-district head knowledge about the duties and authority as PPAT, the number of Sub-district head duties in the government field which cause the affairs of the process of transferring rights to land are neglected and are often delegated to sub-district staff. Furthermore, the PPAT Deed Forms should not be used again since the enactment of the Regulations of the Republic of Indonesia National Land Number 8 year 2012. However, in reality many temporary PPAT or Sub-district heads still use the old forms which are no longer specified in the applicable Regulations. The deed made must be an Authentic Deed as stipulated in Article 1868 of the Civil Code concerning the Authentic Deed, namely a deed which is in the form prescribed by law, made by or before the public officials where the deed is made. On the other hand, the position as a PPAT must be in accordance with PP Number 37 year 1998 concerning the Regulation of the Position of the Land Deed Officials Keywords: Sub-district head Authority; Temporary PPAT; deed